2 - Sociologie D’une Revolte Armee: Le Cas de Libye - Ouannes Moncef (African Sociological Review, 2013)
This article is a sociological reading of events that occurred in libya between 17 february and 20 October 2011. it tries to answer the main question: why did change policy he take a very violent character with 50 000 dead more than 100 000 injured? Why was it monopolzed by radical islamist? and What was the relationship between tribe and the state?